MODEL PENGEMBANGAN MASYARAKAT BERAGAMA - Athoilah aly najamudin; Emi Hidayati; Ginanjar Prastyanto (AT TAMKIN : Jurnal Pengembangan Masyarakat Islam dan Perubahan Sosial, 2023)
The development of religious communities is an interesting research area to study, this is because human behavior always has a relationship with the surrounding community. In practice, society makes religion a way of life. Community development is one of the instruments towards a harmonious community life order. However, recently, there have been many challenges in implementing the empowerment of religious communities, ranging from inter-religious conflicts to radical and conservative understandings of Islam. In this context, this paper finds a model for developing a religious community with the aim of strengthening and disseminating an understanding of community development in the space of a religious community. The approach in this study is to study literature or literature from various references obtained. This paper shows that there are 3 (three) models in the development of religious communities (1) the Medina community development model, (2) the ABCD community development model, (3) the people, centered, participatory community development model, (4) the inter-religious community development model.